Niche markets for sustainable agri-food systems: A systematic review - Kehinde Oluseyi Olagunju; Simone Angioloni; Maurizio Canavari (Heliyon)
The agri-food systems face many global and local challenges, including climate change, environmental degradation, and loss of biodiversity. As the global population continues to rise, the demand for food and other ecosystem services also increases, escalating the pressure on agri-food systems. There is an urgent need to transition agri-food systems’ goals from production efficiency to sustainability to address these challenges. Within agri-food systems, niche marketing has gained prominence in achieving sustainability. Using the PRISMA framework, this study performs a systematic literature review up to November 2024 to gather existing evidence on how niche markets can promote sustainable agri-food systems while also identifying challenges and policy options. To this end, two databases were employed: Web of Sciences and Scopus. Findings from the selected literature (58 articles) indicate that developing niche markets to deliver sustainable agriculture is subject to various challenges related to risk exposure, entry barriers, changing consumer preferences, and institutional context. In general, three main ways through which niche markets can support sustainable agri-food systems were identified. Firstly, niche markets provide financial incentives to encourage farmers to adopt environmentally friendly practices by increasing the price premiums and limiting competitors' market access. Secondly, niche markets facilitate partnerships and networks that enable sharing know-how and best practices, reducing the high cost of transitioning to sustainable production systems. Thirdly, niche markets promote radical innovations and technologies that enable increased economic efficiency and environmental performance. In terms of policy implications, public initiatives fostering the expansion of niche markets in agri-food production should increase financial support, access to credit, and legal recognition of certifications for environmentally friendly products. Other measures include fostering knowledge transfer and networking between farmers and consumers.